COVID-19 related acute genital ulcer: a case report - Jacyntho,Cláudia Márcia de Azevedo (2022)
ABSTRACT Acute vulvar ulcer (Lipschütz’s ulcer) is a rare lesion with local hyperimmunoreactivity triggered by infection, which is characterized by acute, painful, and necrotic ulcerations. This condition is usually found in non-sexually active adolescents, and it resolves spontaneously. We report a case of a 35-year-old woman who was diagnosed with COVID-19 who did not have severe symptoms, but had high levels of D-dimer for 9 days. The COVID-19 diagnosis was followed by the appearance of an acute, necrotic, extremely painful vulvar ulcer, although symptoms caused by COVID-19 had improved. We emphasize the importance of the differential diagnosis to exclude diseases such as Behçet’s syndrome, Sexually Transmitted Infections, as well as the presence of viruses that generally trigger Lipschütz’s ulcer, such as Epstein-Barr virus and cytomegalovirus. No treatment is usually necessary, however, in the present report due to the pain experienced by the patient, we successfully used oral prednisone.